A new flavonol glycoside from the florets of Carthamus tinctorius L. Issue 2 (17th January 2016) - Xie, Xue; Zhou, Jianming; Sun, Lin; Zhang, Hongda; Zhao, Yiwu; Song, Yaling; Wang, Xuejing; Ni, Fuyong; Huang, Wenzhe; Wang, Zhenzhong; Xiao, Wei
Abstract : One new flavonol glycoside, 6-hydroxykaempferol-3- O -β-D -glucoside-7- O -β-D -glucuronide (1 ), together with eight known flavonoids and three known quinochalcones, was isolated from the florets of Carthamus tinctorius L. Their structures were determined by extensive spectroscopic analyses. Their cardioprotective effects against H2 O2 -induced apoptosis in H9c2 cells were also evaluated; compounds1, 2, 4 –5, 7 –10 and12 provided significant protective effects on H2 O2 -induced H9c2 cells at the concentration of 25 μg/mL. Abstract :